Moringa oleifera leaf extract mediated green synthesis of silver nanoparticles and their antibacterial effect against selected gram-negative strains. (April 2023) - Younas, Mehwish; Rasool, Muhammad Hidayat; Khurshid, Mohsin; Khan, Amjad; Nawaz, Muhammad Zeshan; Ahmad, Ijaz; Lakhan, Muhammad Nazim
Abstract: Antibiotic resistance among bacterial infections has become a leading problem in the medical industry. Herein, we have synthesized the silver nanoparticles (AgNPs) from fresh leaves of Moringa oleifera extract. The synthesis was optimized by varying the concentration of AgNO3, plant extract, and contact time. The as-prepared nanoparticles (NPs) were examined by various advanced analytical tools including UV–Vis, FTIR, XRD, SEM-EDS, TEM, DSC and TGA to confirm the morphology, particle distribution, and thermal effect. The antimicrobial potential of AgNPs was determined against selected pathogenic strains including Klebsiella pneumoniae (ATCC® 13883™), Escherichia coli (ATCC® 25922™), Acinetobacter baumannii (ATCC® 19606™), and Pseudomonas aeruginosa (ATCC® 27853™). The ager-well assay showed inhibitory zones in the range of 7–15 mm with MIC value of 250 μg/ml which suggests that strains are sensitive in growth inhibitory conditions. The present work affirms that AgNPs mediated through leaves of Moringa oleifera exhibits a higher antibacterial potential as compared with previous reported studies, and can be used in biomedical science for disinfection applications. Highlights: Silver nanoparticles (AgNPs) synthesized from fresh leaves of plant Moringa oleifera extract. The as-prepared AgNPs were examined by a range of advanced analytical tools. The ager-well assay showed maximum inhibitory zones in the range of 7–15 mm with MIC value of 250 μg/ml. Moringa oleifera mediated AgNPs can be used in biomedical science for disinfection applications.